О строении эндегины пауков Dictyna arundinacea (L.) и Dictyna uncinata Thоr. (сем. Dictynidae) - Пичка, В.Е. (Вестник зоологии, 1975)
Females of the genus Dictyna (the family Dictynidae) are difficult to recognize by their external morphological characters. Their species may be determined exactly by the endegine structure. The structure of the genital apparatuses in Dictyna arundinacea (L.). and D. uncinata Thor. is shown in the pictures.